Requirements for a Robust Animal Model to Investigate the Disease Mechanism of Autoimmune Complications Associated With ARF/RHD - Rafeek, Rukshan A. M.; Sikder, Suchandan; Hamlin, Adam S.; Andronicos, Nicholas M.; McMillan, David J.; Sriprakash, Kadaba S.; Ketheesan, Natkunam (Frontiers in Cardiovascular Medicine, 2021)
The pathogenesis of Acute Rheumatic Fever/Rheumatic Heart Disease (ARF/RHD) and associated neurobehavioral complications including Sydenham's chorea (SC) is complex. Disease complications triggered by Group A streptococcal (GAS) infection are confined to human and determining the early events leading to pathology requires a robust animal model that reflects the hallmark features of the disease. However, modeling these conditions in a laboratory animal, of a uniquely human disease is challenging. Animal models including cattle, sheep, pig, dog, cat, guinea pigs rats and mice have been used extensively to dissect molecular mechanisms of the autoimmune inflammatory responses in ARF/RHD. Despite the characteristic limitations of some animal models, several rodent models have significantly contributed to better understanding of the fundamental mechanisms underpinning features of ARF/RHD. In the Lewis rat autoimmune valvulitis model the development of myocarditis and valvulitis with the infiltration of mononuclear cells along with generation of antibodies that cross-react with cardiac tissue proteins following exposure to GAS antigens were found to be similar to ARF/RHD. We have recently shown that Lewis rats injected with recombinant GAS antigens simultaneously developed cardiac and neurobehavioral changes. Since ARF/RHD is multifactorial in origin, an animal model which exhibit the characteristics of several of the cardinal diagnostic criteria observed in ARF/RHD, would be advantageous to determine the early immune responses to facilitate biomarker discovery as well as provide a suitable model to evaluate treatment options, safety and efficacy of vaccine candidates. This review focuses on some of the common small animals and their advantages and limitations.